CENTRAL CORNEAL THICKNESS AND INTRAOCULAR PRESSURE CHANGES POST- PHACOEMULSIFICATION SURGERY IN GLAUCOMA PATIENTS WITH CATARACT - Hong-Kee, N; Ahmad-Marwan; Julieana, M; Chong; Vivian-Gong; Liza-Sharmini; Azhany, Y (Ceska a slovenska oftalmologie, 2023)
AIMS: To compare the changes of central corneal thickness (CCT) and intraocular pressure (IOP) post-phacoemulsification between cataract patients with and without pre-existing glaucoma. MATERIALS AND METHODS: A prospective cohort study of 86 patients with visually significant cataract: 43 with pre-existing glaucoma (GC group) and 43 without pre-existing glaucoma (CO group). CCT and IOP were evaluated at baseline (pre-phacoemulsification), as well as at 2 hours, 1 day, 1 week and 6 weeks post-phacoemulsification. RESULTS: The GC group have significantly thinner CCT pre-operatively (p = 0.003). There was a steady increase of CCT with the highest peak at 1 day post-phacoemulsification, followed by a steady decline of CCT and back to baseline at 6 weeks post-phacoemulsification in both groups. The GC group demonstrated a significant difference in CCT at 2 hours (mean difference 60.2 μm, p = 0.003) and 1 day (mean difference 70.6 μm, p = 0.002) post-phacoemulsification, compared to the CO group. There was a sudden increase in IOP at 2 hours post-phacoemulsification measured by GAT and DCT in both groups. This was followed by a gradual reduction of IOP, with significant reduction at 6 weeks post-phacoemulsification in both groups. However, there was no significant difference in IOP between the two groups. IOP measured by GAT and DCT showed strong correlation (r > 0.75, p < 0.001) in both groups. There was no significant correlation between GAT-IOP and CCT changes; nor between DCT-IOP and CCT changes in both groups. CONCLUSIONS: CCT changes post-phacoemulsification in patients with pre-existing glaucoma were similar, in spite of having thinner CCT pre-operatively. IOP measurement was not affected by CCT changes in glaucoma patients post-phacoemulsification. IOP measurement using GAT is comparable with DCT post-phacoemulsification.
Keywords: glaukom; Tonometry, Ocular; central corneal thickness; rohovka; Intraocular Pressure; glaucoma; nitrooční tlak; Prospective Studies; tonometrie oční; Phacoemulsification; Glaucoma; Humans; prospektivní studie; fakoemulzifikace; intraocular pressure; katarakta; Cataract; Cornea; lidé